A multicenter validation of the modified brain injury guidelines: Are they safe and effective?. Issue 1 (1st July 2022) - Khan, Abid D.; Lee, Janet; Galicia, Kevin; Billings, Joshua D.; Dobaria, Vishal; Patel, Purvi P.; McIntyre, Robert C.; Gonzalez, Richard P.; Schroeppel, Thomas J.
Abstract : This multicenter trial shows that the modified Brain Injury Guidelines are safe to implement and will lead to substantial improvements in resource utilization for any institution that adopts them to treat patients with traumatic brain injury and intracranial hemorrhage. Abstract : BACKGROUND: The modified Brain Injury Guidelines (mBIG) are an algorithm for treating patients with traumatic brain injury and intracranial hemorrhage by which selected patients do not require a repeat head computed tomography, a neurosurgery consult, or even an admission. The mBIG refined the original Brain Injury Guidelines (BIG) to improve safety and reproducibility. The purpose of this study is to assess safety and resource utilization with mBIG implementation. METHODS: The mBIG were implemented at three Level I trauma centers in August 2017. A multicenter retrospective review of prospectively collected data was performed on adult mBIG 1 and 2 patients. The post-mBIG implementation period (August 2017 to February 2021) was compared with a previous BIG retrospective evaluation (January 2014 to December 2016). RESULTS: There were 764 patients in the two study periods. No differences were identified in demographics, Injury Severity Score, or admission Glasgow Coma Scale score. Fewer computed tomography scans (2 [1, 2] vs. 2 [2, 3], p < 0.0001) and neurosurgery consults (61.9% vs. 95.9%, p < 0.0001) were obtained post-mBIG implementation. Hospital (2 [1, 4] vs. 2 [2, 4], p = 0.013) and intensive care unit (0 [0, 1] vs. 1 [1, 2], p < 0.0001) length of stay were shorter after mBIG implementation. No difference was seen in the rate of clinical or radiographic progression, neurosurgery operations, or mortality between the two groups. After mBIG implementation, eight patients (1.6%) worsened clinically. Six patients that clinically progressed were discharged with Glasgow Coma Scale score of 15 without needing neurosurgery intervention. One patient had clinical and radiographic decompensation and required craniotomy. Another patient worsened clinically and radiographically, but due to metastatic cancer, elected to pursue comfort measures and died. CONCLUSION: This prospective validation shows the mBIG are safe, pragmatic, and can dramatically improve resource utilization when implemented. LEVEL OF EVIDENCE: Therapeutic/Care Management; Level III. Abstract :